Answer:
The solution of the equation
( 0.4 ,-3)
Step-by-step explanation:
Explanation:-
Step(i):-
Given system of equations
10 x+3 y = −5 ...(i)
- 5 x - 4 y = 10 ...(ii)
Multiply (i) with '5'
10 × 5 x + 3×5 y = - 25
50 x + 15 y = 25 ...(iii)
Multiply (ii) with '10'
-5 × 10 x - 4×1 0 y = 100
- 50 x - 40 y =100 ...(iv)
Step(ii):-
Solving (iii) and (iv)
50 x + 15 y =- 25
- 50 x - 40 y =100
- 25 y = 75
Dividing ' - 25' on both sides, we get
y = -3
substitute y = -3 in equation (i) , we get
10 x+3 y = −5
10 x - 9 = - 5
10 x = -5 + 9
[tex]x = \frac{4}{10}[/tex]
x = 0.4
Final answer:-
The solution of the equation ( 0.4 ,-3)